PENGENDALIAN DAN PENINGKATAN KUALITAS HIDUP PENDERITA LEPRA BERBASIS TEKNOLOGI MOLEKULER DI UNIT UJI TROPICAL DISEASE DIAGNOSTIC CENTRE UNIVERSITAS AIRLANGGA - Aksono, Bimo (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2014)
The aim of community service activities through a U-UJI TDDC will be conducted strain mapping M. leprae (genetic mapping) and TTC-based maping region mutation patterns of drug rifampin rpoB gene-based regions. The be- nefits of this activity is an increase in quality of life for the leprosy both socially and economically because of the application of molecular technology could help early detection of regional-based Variable Number Tandem Repeat (VNTR) of the TTC and rifampin-resistant gene (rpoB gene) and is expected to occur later therapeutic action will accelerate the decline in the incidence and cure the patient. Materials in this study isolates M. leprae from skin incision swabs, nasal mucosa and skin lesions biopisi of leprosy who come from a few enclaves leprosy in Sumberaji-Lamongan District. Criteria for patient sample is still relatively new or are in treatment. Based on these criteria finally set 17 sample patients, whether included Pseudobasiler type (1 sample) and Multibasiler (16 samples). The method used is a nested PCR using specific primers from the region of the TTC, LP and rpoB. The results of nucleotide sequencing of both the sequence of the region of TTC, LP and rpoB region using GENETIX Mac software ver. 9.0. Community service activities based on the application of molecular technology by U-Uji TDDC, Airlangga University in endemic areas, especially infectious diseases in leprosy Sumberaji Lamongan District, from the results of PCR and nucleotide sequence analysis of a sample selected patients indicates that the bacteria M. leprae in Sumberaji consists of three strains of M. leprae based on TTC-15, TTC-23 and TTC-28, while the analysis of the rpoB region of the mutation was not found either in CAG513-Gln, GAT516-Asp, CAC526- His, and TCG531-Ser-Leu CTG533, this indicates that the isolates of M . leprae found in the leprosy in Sumberaji Lamongan district are sensitive to rifampin treatment. The results of this mapping can be used as a reference that rifampin treatment can be used for therapy MDT on leprosy in Sumberaji Lamongan district